Endovascular surgery in patients with coronary artery disease in combination with cancer - B. G. Alekyan; A. A. Gritskevich; N. G. Karapetyan; D. V. Ruchkin; A. A. Pechetov; P. V. Markov; B. N. Gurmikov; N. L. Irodova; L. G. Gyoletsyan; E. V. Tokmakov; A. V. Galstyan; A. Sh. Revishvili (Южно-Российский онкологический журнал, 2024)
Purpose of the study. To analyze the long-term results from various strategies of endovascular treatment for coronary artery disease (CAD) in patients concomitant with cancer.Patients and methods. 74 patients with both CAD disease and cancer were treated in A. V. Vishnevskiy National Medical Research Center of Surgery from 01/01/2018 to 12/31/2022. By a multidisciplinary council, patients were divided into three groups: group 1 (n = 39) – staged treatment: percutaneous coronary intervention (PCI) is the first stage, the second is surgical treatment of cancer; group 2 (n = 14) – staged treatment: the first stage was surgical treatment of cancer, and the second stage was PCI; group 3 (n = 21) – PCI and open surgery were performed on the same day.Results. In the immediate period, 3 (4.0 %) deaths were observed: 2 (5.1 %) in group 1, 1 (4.8 %) in group 3, the cause of which was complications arising after oncological surgical interventions. One (2.6 %) patient from group 1 had acute myocardial infarction (AMI) due to acute stent thrombosis in the left anterior descending artery (LAD). The patient underwent successful emergency PCI. In the long-term period, 15 (25.4 %) patients died, out of which 11 (18.7 %) from progression of cancer, and 4 (6.7 %) from other causes. Among the major cardiovascular complications, the following were observed: 1 (3.2 %) AMI in group 1 and 1 (7.1 %) in group 2.Conclusion. In the long-term follow-up period, the leading cause of death (73,3 %) was progression of cancer. There were no detected from deaths AMI, which confirms the importance and feasibility of myocardial revascularization in this severe group of patients. PCI in patients with coronary artery disease in combination with cancer allows for effective and safe surgical treatment of malignant pathology without cardiac mortality both in the immediate and long-term follow-up periods.